2020
DOI: 10.1111/jjns.12362
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of objective physical activity and quality of life in living donor liver transplant recipients

Abstract: Aim: The aims of this study were to: (a) describe the physical activity (PA) and quality of life (QOL) in living donor liver transplant (LDLT) recipients pre-operatively and at 3 months and 6 months post-operatively; (b) compare PA and QOL at 6 months post-operatively with a healthy control group; and (c) explore pre-operative factors that predict PA changes. Methods: Patients over 20 years of age who were undergoing LDLT were recruited. PA was measured based on the number of steps/day and time spent performin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Less-than-optimal adherence was associated with readmissions to the hospitals in 50% of patients with LT and increased health care costs up to $100 billion in the US and in many countries (Oliveira et al, 2016). Indeed, 8%to 66% of LT recipients had poor medication compliance (Ko et al, 2018), 47% of recipients had poor follow-up compliance (Stilley et al, 2010), 20.5% of the recipients had poor compliance with maintaining a reasonable diet (Ko et al, 2016; Wei & Liu, 2009), 28% of the recipients had poor self-monitoring compliance (Wei & Liu, 2009), 23% to 29% of the recipients had a poor psychological adjustment ability (Annema et al, 2018), and most recipients had poor exercise behaviors (Tanaka et al, 2020). Appropriate self-management of transplant recipients can improve their medical compliance, and prevent and/or aid in the management of potential health problems (Kallwitz et al, 2013; Serper et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Less-than-optimal adherence was associated with readmissions to the hospitals in 50% of patients with LT and increased health care costs up to $100 billion in the US and in many countries (Oliveira et al, 2016). Indeed, 8%to 66% of LT recipients had poor medication compliance (Ko et al, 2018), 47% of recipients had poor follow-up compliance (Stilley et al, 2010), 20.5% of the recipients had poor compliance with maintaining a reasonable diet (Ko et al, 2016; Wei & Liu, 2009), 28% of the recipients had poor self-monitoring compliance (Wei & Liu, 2009), 23% to 29% of the recipients had a poor psychological adjustment ability (Annema et al, 2018), and most recipients had poor exercise behaviors (Tanaka et al, 2020). Appropriate self-management of transplant recipients can improve their medical compliance, and prevent and/or aid in the management of potential health problems (Kallwitz et al, 2013; Serper et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In past research with post‐liver‐transplant patients, PA was measured by self‐reported PA questionnaires and was lower than in the general healthy population (Kotarska et al, 2014; Masala et al, 2012). In other studies that measured PA using an accelerometer, the PA levels observed were mainly sedentary or light‐intensity PA, with few or no activities of moderate or higher intensity (Tanaka et al, 2020; van den Berg‐Emons et al, 2006). Nevertheless, moderate‐to‐vigorous‐intensity PA remains the focus of PA studies in post‐liver‐transplant patients, and few studies have measured sedentary behaviors and low‐intensity PA (Berben et al, 2019).…”
Section: Introductionmentioning
confidence: 96%
“…However, the SQUASH currently does not include items on very light‐intensity PA (i.e., below 2 METs) or sedentary behavior. Still, researchers have commonly observed post‐liver‐transplant patients engage in sedentary behavior (Tanaka et al, 2020). Thus, the SQUASH needs modifications in order to be capable of measuring the extent of sedentary behavior and light‐intensity PA.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity (PA) after LT is effective in preventing the onset and severity of metabolic syndrome, including hypertension and obesity, which are long-term post-transplant complications, and improving physical function and quality of life (QOL) [7][8][9]. A study on PA and depression in kidney transplant recipients 6 years after transplant revealed that higher PA levels were associated with a lower risk of depression [10].…”
Section: Introductionmentioning
confidence: 99%